Analisis Komponen Makna dan Makna Leksem dalam Kontruksi Kalimat Uli Al- Amr dan Amir Al- Mu'minin - Hidayatullah, Moch. Syarif (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2008)
The research target is to explain semantic field of UIi al-Amr and Amir al-Mu'minin in Arabic, especially, which is found in Al-Qur'an and Hadis. The relationship among lexemes is paradigmatic The analysis of each lexeme in the sentence construction shows the meaning ofeach lexeme has synonymous meaning with other at one time and has diherent meaning in other time. Each lexeme could has negative and positive connotation. The connotations are depending on its context and collaration, On the analysis of sentence construction, there are polysemy and homonymy tendency of those lexemes.